LECTINOCHEMICAL CHARACTERISTICS OF CELLULAR ELEMENTS OF ERYTRIBLASTIC INSULA OF RATS’ RED BONE MARROW IN ADMINISTRATION OF CRYOPRESERVED PLACENTA - Білаш, С.М.; Борута, Н.В.; Старченко, І.І. (World of Medicine and Biology, 2017)
With the aid of lectinogistochemical research, a comparative analysis of the composition of carbohydrate residues on the structural elements of the red rats’ erythroblastic insula was carried out. It was established that the distribution of carbohydrate residues on the structural elements of the erythroblast island depends on the inductors of influence, which change the carbohydrate specificity on the structural elements of the erythroblast insula.